PERANCANGAN APLIKASI E-RAPOR BERBASIS WEB UNTUK MENDUKUNG EVALUASI PEMBELAJARAN DI MADRASAH TA’HILIYAH IBRAHIMY SUKOREJO SITUBONDO - Padlan Al Munar; Abdus Somad (Jurnal Riset Sistem Informasi, 2025)
Advances in information technology have provided significant opportunities to improve the efficiency of various aspects, including learning evaluation in education. This research aims to design and develop a web-based E-Rapor application to support student grade management at the Ibrahimy Sukorejo Madrasah Ta'hiliyah (MTI) Situbondo. The previously manual evaluation process presented various challenges, such as the risk of data errors, processing delays, and a lack of transparency. This application was designed using the Waterfall method, utilizing PHP and MySQL technology to manage data centrally and efficiently. The results show that the E-Rapor application can improve grade management efficiency, facilitate teachers' data recapitulation, and provide transparent online access for students and parents. This implementation supports the Independent Curriculum policy of adopting digital technology in the educational environment. This application is expected to positively contribute to a more effective learning evaluation process and inspire other educational institutions to implement similar innovations.